ISLAM NUSANTARA: AMBIGUITY, CULTURAL STRATEGY OR ORIGINALITY : (A Historical Studies) - Abdul Aziz; Debi Arlianto (Batuthah: Jurnal Sejarah Padaban Islam, 2023)
Islam Nusantara is a new term in Indonesia. The opposing group views it as a form of Islamic division, and the pro group considers it a strategy for Islamic da'wah with a slogan of moderation and a cultural approach. Islam Nusantara is defined as Islam that is friendly, inclusive, dynamic, and friendly with a diverse cultural, sub-cultural and religious environment. From this meaning, the question arises from this ambiguity: "does the Islam brought by the Prophet not have the characteristics mentioned above, so it needs a discourse on Islam Nusantara? Or did it just happen because of the problem of syncretism and local cultural infiltration? It is a fundamental question that needs to be cleared. This study uses a social and historical approach to analyze the origin, meaning, and purpose of Islam Nusantara from the perspective of Indonesian society. Islam Nusantara is not a new issue. The identity of Islam has been popular since Islamization. The researcher concludes that the terminology of Nusantara Islam has political and theological content. That is the discourse of certain Islamic rulers and organizations dealing with the current epidemic of radicalism and extremism in religion. Originality is the primordial value of Islam that is not bound by time and place; inclusive, dynamic, and moderate. At the same time, the cultural strategy is a dialogue effort between Islam and time and place. Islam Nusantara needed to develop and change according to the demands of the times.